Publish or Perish: Perspectives from the APJHM for health managers - David Briggs (ACHSM, 2018)
The term 'publish or perish' is familiar to most of us engaged in some way in academia and reflects the mantra that to have a successful career as a teacher, researcher and all-round academic wanting to be recognised as an expert in your discipline requires you to be well and regularly published. This directive also has added implications to not publish in 'any journal' but in ones that have high impact factors. This suggests that they have recognised quality articles that have been peer reviewed, have rigour in the editorial process and, therefore are difficult to obtain publication in, particularly for students and emerging researchers. Progression of careers are dependant on this mantra and, we all want to ensure that the quality of our research, our science is of the best standard.....